2016
DOI: 10.1007/s10163-016-0519-7
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal effects of manure management and feeding strategies on hydrogen sulphide emissions from stored dairy manure

Abstract: The influence of temperature and storage time on hydrogen sulphide (H 2 S) emissions from two different dairy manures was investigated over four seasons in 2012. Two separate experiments were conducted using dairy manure;(1) water baths at 0, 5, 10, 15, 20, 25 and 30°C that were incubated for 15 h, and (2) 28-day batch experiment under room temperature. The headspace H 2 S concentration increased exponentially after 15°C and reached a maximum of 3.1 mg/L at 30°C. After the 4th day of storage, dairy manure emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…The temperature affects the urease activity in the excrement and a higher temperature increases the urease activity, accelerating urea decomposition into NH 3 . Formation and release of H 2 S from manure are also expected to be affected by the temperature, since the decomposition of S-containing organic compounds in manure is enzyme-dependent 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The temperature affects the urease activity in the excrement and a higher temperature increases the urease activity, accelerating urea decomposition into NH 3 . Formation and release of H 2 S from manure are also expected to be affected by the temperature, since the decomposition of S-containing organic compounds in manure is enzyme-dependent 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schiffman et al (2001) identified 331 different inorganic and volatile organic compounds (VOCs) from a swine facility. The most significant trace gas is hydrogen sulfide (H 2 S), which can cause health problems to workers and animals (Andriamanohiarisoamanana et al, 2017). Other important sulfur gases include mercaptans and disulfides (Casey et al, 2006).…”
Section: Husbandry and Poultry/waste Systemsmentioning
confidence: 99%